2008
DOI: 10.1109/jlt.2008.925624
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Over-MMF Techniques—Part I: RF to Microwave Frequency Systems

Abstract: Abstract-Recent work on radio over multimode fiber transmission, for the support of wireless LANs and current cellular systems operating at below 6 GHz, has shown that excellent performance (e.g. spur-free dynamic range well in excess of 100 dB.Hz2/3) can be achieved. However, here it is shown that for multi-system operation, spurious emissions may be more of a restriction than meeting good signal quality requirements (such as low error vector magnitude). Initial results are reported for error vector magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…However, the efficiency depends on the frequency of the RF signal used and polarization voltage applied on the MZM. Power amplifier (PA) is the most power-consuming element in modern transmitter architectures [1,2]. High-efficiency power amplifier can be obtained through different matching networks, such as Class-E, Class-F, Class-J, and crossover among them [2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficiency depends on the frequency of the RF signal used and polarization voltage applied on the MZM. Power amplifier (PA) is the most power-consuming element in modern transmitter architectures [1,2]. High-efficiency power amplifier can be obtained through different matching networks, such as Class-E, Class-F, Class-J, and crossover among them [2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…The commercial packaged GaN devices are composed of the intrinsic die and gold wires connected to the terminal of the package. The GaN HEMT's nonlinear capacitance is very important for harmonic control circuit (HCC) design [2][3][4][5]. The Cree'GaN HEMT model is based on Fager-Statz's 13-Element MESFET model [8].…”
Section: Gan Hemt Model With Nonlinear Capacitancementioning
confidence: 99%
“…Some tests were carried out for an active RFID technology at the 2.4 GHz band. The transmission of UMTS signals at ~2 GHz over a VCSEL-MMF link simultaneously with GSM900, GSM1800, and IEEE 802.11g signals was demonstrated in [9]. In that work, the UMTS performance results showed that the adjacent channel leakage ratio (ACLR) requirements are more difficult to meet when the three other signals are present.…”
Section: Introductionmentioning
confidence: 99%
“…However, not much work has been done at frequencies higher than VCSEL's 3-dB cut-off frequency. A 22 Mbps transmission at 40 GHz was demonstrated using a mode-locked laser, but only 4 MHz RF bandwidth was available with such a laser 7 . In this work, we managed to obtain up to 6 Gbps 64-QAM data transmission using a 1.75 GHz bandwidth at several bands between 24-28 GHz using an in-house developed VCSEL array 8 and a customized wideband driving amplifier 9 .…”
Section: Introductionmentioning
confidence: 99%